PERENCANAAN ARSITEKTUR SISTEM INFORMASI PT. MA’SOEM ARIAS DENGAN MENGGUNAKAN ORACLE ENTERPRISE ARCHITECTURE FRAMEWORK - Soni Ayi Purnama (Jurnal Accounting Information System (AIMS), 2018)
Utilization of information systems and information technology is needed in supporting business processes of a company, because the information system is one of the important things in the key to success of a company. Along with the development of information systems have an information system architecture model, where the information system architecture is necessary to plan the information system architecture to be built in the future, where the information system architecture as a spear to improve the competitiveness of a company with other companies.             PT. Ma'soem Arias is one of Pertamina lubricant distributor in West Java. The business activities carried out are to sell Pertamina lubricants to direct customers and direct lubricant procurement from Pertamina's producers. PT. Ma'soem Arias until now in carrying out its business process has not used the information system so needed an Enterprise Architecture planning for PT. Ma'soem Arias.Enterprise architecture model used in this research is by using Oracle Enterprise Architecture Framework (OEAF) model. The advantages of OEAF is to use object oriented concept, where the concept approaches the problem from the perspective of the object and not the perspective of the functional so it is easy to be understood. The method used is Oracle Architecture Development Process (OADP) method, where OADP method has several stages, ie from start of study about business architecture, architecture vision, current state architecture and future state architecture.The result of this research is recommendation of information system of PT. Ma'soem Arias is a blueprint for enterprise architecture planning that succeeds in defining 4 main business processes, the data architecture produces 24 entities, 4 applications and for its technological architecture produces technology architecture proposal.